Toxicity Evaluation of Household Detergents and Surfactants Using Zebrafish - Han, Jae-Hoon; Jung, Sang-Kyu (Biotechnology and bioprocess engineering, 2021)
There are concerns regarding the toxicity of household detergents to humans and aquatic organisms. There are various types of surfactants, which are the main components of detergents, and each detergent product has a different formulation. Therefore, high-throughput technologies capable of analyzing a large number of samples rapidly and accurately are required for research on detergent toxicity. In this study, image analysis techniques were used to quantify the locomotor activities from captured images using larval zebrafish ( Danio rerio ). When the 135-min time-lapse imaging was completed, the damage to the body of the animals was examined using a microscope. Additionally, we determined the animal survival and LC 50 . Nonionic decyl glucoside (APG-C10), one of the alkyl polyglucosides (APGs), exhibited the lowest toxicity, whereas linear alcohol ethoxylate (LA-9) exhibited the highest toxicity. AOS (α-olefin sulfonate), LAS (linear alkylbenzene sulfonate), and APG-600 showed moderate toxicity between LA-9 and APG-C10. Commercial detergents exhibited various degrees of toxicity, and there was a linear relationship (R 2 = 0.776) between locomotor activity and survival percentage of animals.